2014
DOI: 10.1142/s0218863514500015
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenide Brillouin lasers

Abstract: In recent years, chalcogenide glasses have emerged as a material platform for nonlinear signal processing and mid-infrared photonics. In addition, high Brillouin gain of these soft glasses enable compact and highly efficient Brillouin lasers (BL). We review recent progress on chalcogenide BL, compare fiber and waveguide laser geometries, and discuss the potential of chalcogenide platform for compact and high-coherence light sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This is particularly true in integrated photonics where both optical and acoustic modes can be confined in sub-wavelength cross-sections. Recently, intense interest in bringing AO-based devices to integrated photonics have yielded isolators [2][3][4][5], amplifiers and lasers [6][7][8][9][10][11], microwave photonic devices [10,12,13], modulators [3,4,[14][15][16], and even optical phased arrays [17].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in integrated photonics where both optical and acoustic modes can be confined in sub-wavelength cross-sections. Recently, intense interest in bringing AO-based devices to integrated photonics have yielded isolators [2][3][4][5], amplifiers and lasers [6][7][8][9][10][11], microwave photonic devices [10,12,13], modulators [3,4,[14][15][16], and even optical phased arrays [17].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenide glass (ChG) fibers show great potential for a variety of mid-infrared (MIR) applications such as laser transmission, 1-3 nonlinear optics, [4][5][6][7][8] and thermal image delivery, [9][10][11] mainly due to their low transmission loss in the MIR, high optical nonlinearity as well as good flexibility. Compared with Se and Te-based ChGes, S-based ones usually have higher power handling ability because of the stronger bonding strength between constituent elements.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These glasses have been shown to possess $100 times larger nonlinear Kerr e®ect and transmit to longer wavelengths in the IR region than silica and°uoride glasses. 3 High index contrast, transparency in the near IR spectral region and large Kerr e®ect make these glasses a potential candidate for the fabrication of low cost photonic devices on a thin¯lm for several applications including optical components for focusing and collimation, nonlinear optics, 4,5 on-chip based sensors, 6 chalcogenide brillouin lasers 7 and all optical switching. 8 Richardson et al have demonstrated that Chalcogenide materials can be (a) highly°exible (b) appropriately tailorable solutions for highly speci¯c, sensitive sensors in integrated form.…”
Section: Introductionmentioning
confidence: 99%